Irregular Grid Raycasting Implementation on the Cell Broadband Engine - Cox, Guilherme; Maximo, Andre; Bentes, Cristiana; Farias, Ricardo (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2009)
Direct volume rendering has become a popular technique for visualizing volumetric data from sources such as scientific simulations, analytic functions, medical scanners, among others. Volume rendering algorithms, such as raycasting, can produce high-quality images, however, the use of raycasting has been limited due to its high demands on computational power and memory bandwidth. In this paper, we propose a new implementation of the raycasting algorithm that takes advantage of the highly parallel architecture of the Cell Broadband Engine processor, with 9 heterogeneous cores, in order to allow efficient raycasting of irregular datasets. All the computational power of the Cell BE processor, though, comes at the cost of a different programming model. Applications need to be rewritten, which requires using multithreading and vectorized code. In our approach, we tackle this problem by distributing ray computations using the visible faces, and vectorizing the lighting integral operations inside each core. Our experimental results show that we can obtain good speedups reducing the overall rendering time significantly.